Undergraduate Physical Education Students’ Technological Pedagogical Content Knowledge - La Kamadi La Kamadi; Ishak Bachtiar; Silatul Rahmi (Seminar Nasional LP2M UNM, 2022)
Abstrak. Physical education program in colleges must prepare students to be future physical education teachers who have knowledge of relevant technology integration, pedagogical skills, and discipline-specific knowledge in order to enhance students learning. The purpose of this study was to identify the Technological Pedagogical Content Knowledge (TPACK) competence of undergraduate physical education students. The research design used in this study is a survey. The research participants are 120 undergraduate students studying physical education in Makassar city. The participants were selected by purposive sampling technique. The data of students’ TPACK were collected by using TPACK questionnaire. The study results showed that students’ TPACK competence were high. The results of the study also revealed that there was no significant difference between male and female students even though the scores of female students were higher than the scores of male students. In addition, there was no significant difference between the scores of public and private university students. Kata Kunci: Technology; Physical Education; Undergraduate Student.